Immunogenetic Aspects of Febrile Convulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Investigators in Genetics, Pediatrics, Neurology, and Immunology, at Mansoura Un., Mansoura, Egypt found a gene frequency of 0.284 (c.f.